Coastal Erosion Dynamics and Protective Measures in the Vietnamese Mekong Delta - Tran Van Ty; Dinh Van Duy; Lam Tan Phat; Huynh Vuong Thu Minh; Nguyen Truong Thanh; Nguyen Thi Ngoc Uyen; Nigel K. Downes (Journal of Marine Science and Engineering, 2024)
The dynamic shifts in shorelines due to erosion and deposition have become a significant challenge in coastal zone management, particularly in the context of climate change and rising sea levels. This paper evaluates the shoreline protection and efficiency of various wave-reducing breakwaters in the Vietnamese Mekong Delta. The delta exemplifies the coastal erosion issue faced by deltas worldwide. Landsat satellite images were used to establish a coastal development map for the period 2000 to 2022. The wave data in front and behind the breakwaters were analyzed to assess the wave reduction efficiency of various breakwater structures. Our results reveal that coastal erosion is deeply concerning, with almost 40% of the coastline experiencing severe erosion. Hotspot areas have been observed to reach annual erosion rates of nearly 95 m per year. The majority of provinces have adopted protective measures, with 68% of affected shorelines protected to some degree. Our results show breakwaters to be highly effective in reducing wave height, with a 62% reduction in waves reaching the shore. The process of creating offset has taken place in the area from the breakwater back to the mainland, with the rate of increase in compensation also quite fast at up to 3.1 cm/month. The stability of the pile–rock is very high; however, it is necessary to add rock to compensate for the settlement of the rock part.